ETIKA BERBISNIS DALAM KEWIRAUSAHAAN PENDIDIKAN MASYARAKAT - Hertina Agustina; Ilham Fauzi; Ira Pradita Yasmin (Universitas Negeri Medan, 2018)
Business is carried out by humans with humans which means good norms or values carry over in business life. In practice, a businessman prefers to use / relate to good quality companies in all aspects. Business ethics is broader than the provisions governed by law which aims to provide moral awareness and provide good behavior. To form a society that has a good entrepreneurial spirit, an entrepreneurial education process is needed in the community. Community Education is one of the best alternatives in carrying out the process of introduction to the supervision of entrepreneurship by the community. Entrepreneurship training for unemployed people in urban areas will give birth to new entrepreneurial candidates who are expected to be able to create their own jobs so as to reduce the number of unemployed